MUSIK SEBAGAI MEDIA TAFAKUR DALAM MEMBANGUN KESADARAN SPIRITUAL MAHASISWA MUSLIM - Desti Nurhauliah; Destiani Renata Putri; Intan Salsabila; Renata Rosalinda; Hilman Taufiq Abdillah (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
The digital era has transformed the accessibility of music through various streaming platforms, making it an integral part of students’ daily lives. This study aims to analyze the role of music as a medium of tafakur (contemplation) in fostering spiritual awareness among Muslim university students. The research employs a descriptive qualitative approach using a questionnaire survey method involving 104 Muslim students in West Java who regularly listen to music. Data were collected through a Google Form questionnaire and analyzed using percentage-based calculations and descriptive interpretation of the findings. The results indicate that the majority of respondents perceive music not only as entertainment but also as a medium for self-reflection, emotional regulation, and spiritual strengthening. Both religious and non-religious songs are considered capable of conveying meaningful messages that encourage reflective contemplation. Therefore, music can function as a medium of tafakur that supports the development of spiritual awareness among Muslim students in the digital era.